DCI Banks. Season three [videorecording (DVD)] - Tompkinson, Stephen, 1965-; Lowe, Andrea, 1975-; Catz, Caroline; Robinson, Peter, 1950-; Robinson, Peter, 1950-; Robinson, Peter, 1950- (Distributed in the USA and Canada by Warner Home Video, 2015)
Will Detective Chief Inspector Alan Banks and Detective Sergeant Annie Cabbot ever get their relationship together? Or will three wrenching crimes and the investigation of Detective Investigator Helen Morton keep them forever out of sync? Welcome back to the hit crime series set in a bucolic Yorkshire town, where you would never expect social workers to abduct a young boy ... never imagine finding a murdered journalist in a holiday chalet ... never dream that the daughter of DCI Banks would be kidnapped. Will his family, his team and his romance survive?--Container